Canadian Association of Gastroenterology Practice Guideline for Clinical Competence in Diagnostic and Therapeutic Endoscopic Retrograde Cholangiopancreatography. (1st September 1997) - Cockeram, Alan
Abstract : This Practice Guideline is intended to assist individuals, training programs and credentialling bodies in understanding the training for and application of endoscopic retrograde cholangiopancreatography (ERCP), as well as in designating credentialling and maintenance of competence. The Canadian Association of Gastroenterology (CAG) Practice Guideline on training and credentialling provides the necessary background (1). Many of the principles outlined have been previously accepted by CAG (2).